A Semi–automated Approach for Generating Sequence Diagrams from Arabic User Requirements Using a Natural Language Processing Tool - Alami, Nermeen; Arman, Nabil; Khamayseh, Faisal (IEEE Explore, 2017)
A sequence diagram is one of UML models that are usually used within the analysis phase in software system development. Since generating such sequence diagrams is performed manually, automated or semi-automated support is beneficial in providing important and practical help. In this paper, a new semi-automated approach for generating sequence diagrams from user requirements written in Arabic is proposed. In this novel approach, the used Arabic requirements are parsed using a natural language processing tool to generate corresponding part of speech. A set of proposed heuristics are to be applied to obtain the sequence diagram components; objects, messages and work flow transitions (messages). The generated sequence diagram is represented using XMI to be drawn using sequence diagrams drawing tools. Using three different case studies as a benchmark from Isra Computer and Programming Company, the proposed approach is evaluated in terms of correctness and completeness of participants and messages exchanged between them.
Keywords: Unified Modeling Language (UML), Automated Software Engineering, Sequence Diagram